Investigation of the global transportation of Culicoides biting midges, vectors of livestock and equid arboviruses, from flower-packing plants in Kenya - Stokes, J.E.; Labuschagne, K.; Fèvre, Eric M.; Baylis, M. (Wiley, 2026)
In recent decades there has been a huge increase in the export of cut flowers from countries in Africa and elsewhere to European flower markets, with the vast majority first entering the Netherlands for local use or for export. Coincidentally, three significant livestock disease outbreaks caused by viruses associated with Africa or other tropical regions were first detected in the Netherlands (bluetongue virus serotype 8 (BTV-8), 2006, and BTV-3, 2023) and in western Germany about 200 km from the Netherlands border (Schmallenberg virus, SBV, 2011). This study aimed to determine whether Culicoides biting midges (Diptera: Ceratopogonidae), the vectors of BTV and SBV, are present within flower-packaging plants in East Africa, and therefore whether Culicoides could be unknowingly exported during the shipping of cut flowers. Field sampling was undertaken at a flower-packaging facility in Kenya, East Africa. The facility undertook all stages of cut flower production from maintaining rootstock through to packaging and shipping to an airport for international export. Trapping was undertaken at each stage of production (rootstock, propagation, inside growing greenhouses, in the packing-house, inside cold-storage rooms, during transportation) using Centers for Disease Control and Prevention (CDC) Light Emitting Diode (LED) light traps. Hand-held aspirators were used to obtain individual insects directly from flowers and around composting sites, while emergence traps studied insect emergence from compost, leaf litter and flowers discarded at quality control checkpoints. A maximum nightly catch of 269 Culicoides was identified on a half-acre smallholding, containing 15 ruminants and 40 birds, located 20 m from the nearest greenhouse. The greatest numbers of Culicoides were trapped at a pond (n = 23) and leaf-litter compost site (n = 19) within the curtilage of the flower-packaging plant. Of the seven greenhouses sampled, three had Culicoides trapped overnight (mean = 4, range: 1–9), and no Culicoides were trapped in the propagation units. No Culicoides were trapped in the pack house, cold-store, or during transportation of the flowers to the airport for shipment. No Culicoides emerged from emergence traps or were trapped when aspirating directly from flowers. This is the first study to investigate whether Culicoides are present within flower packaging plants in Africa. The results highlight that although present in small numbers both outside and within greenhouses, the presence of Culicoides declined with each stage of production. Therefore, the risk of exporting Culicoides with packaged cut flowers is non-zero but likely very small.